Trypanocidal Activity of Some Medicinal Plants Against the Epimastigotes of Trypanosoma cruzi - AR Gohari; S Saeidnia; A Hadjiakhoondi; A Naghinejad; T Yagura (Journal of Medicinal Plants, 2008)
Background: Some of medicinal plants are a potential source of new drugs to improve the treatment of Chagase disease whose treatment is still a challenge. Here in this screening, the in vitro trypanocidal activity of some fractions for 16 medicinal plants, collected from the northern part of Iran, has been reported.